1991
DOI: 10.1080/07315724.1991.10718174
|View full text |Cite
|
Sign up to set email alerts
|

Mineral requirements of low-birth-weight infants.

Abstract: The minerals calcium (Ca), magnesium (Mg), and phosphorus (P) are essential for tissue structure and function. Recent studies have resulted in a more rational approach to the management of mineral intake in preterm infants receiving parenteral nutrition (PN) and enteral nutrition (EN). For preterm infants requiring PN, the use of PN solutions with a Ca content of 1.25-1.5 mmol/dl (50-60 mg/dl), a P content of 1.29-1.45 mmol/dl (40-45 mg/dl), and an Mg content of 0.2-0.3 mmol/dl (5-7 mg/dl) is supported by stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 121 publications
(138 reference statements)
0
17
0
1
Order By: Relevance
“…These To minimize the risk of precipitation from increased concentrations of Ca and P in situations where the infant is being fluid restricted, recommendations for Ca and P intake are based on concentration of milligrams per deciliter of PN solution rather than in the amount of milligrams per kilogram in the patient. 28,29 There are no documented major complications associated with the currently recommended higher Ca and P intake for infants receiving PN. Serial abdominal ultrasound examinations showed that biliary sludge did not occur with greater frequency in infants receiving the higher Ca, P solution compared with those with lower mineral intake.…”
Section: Role Of Calcium and Phosphorusmentioning
confidence: 97%
See 1 more Smart Citation
“…These To minimize the risk of precipitation from increased concentrations of Ca and P in situations where the infant is being fluid restricted, recommendations for Ca and P intake are based on concentration of milligrams per deciliter of PN solution rather than in the amount of milligrams per kilogram in the patient. 28,29 There are no documented major complications associated with the currently recommended higher Ca and P intake for infants receiving PN. Serial abdominal ultrasound examinations showed that biliary sludge did not occur with greater frequency in infants receiving the higher Ca, P solution compared with those with lower mineral intake.…”
Section: Role Of Calcium and Phosphorusmentioning
confidence: 97%
“…5,6,[25][26][27][28] Early studies of infants with nutritionrelated bone disease frequently report the presence of hypophosphatemia, elevated serum alkaline phosphatase activity, decreased urinary P, and increased urinary Ca loss. These findings are consistent with the presence of mineral deficiency, particularly P deficiency.…”
Section: Role Of Calcium and Phosphorusmentioning
confidence: 99%
“…Koo et a1 (9) first demonstrated the need for higher doses of Ca and P in a study of parenteral mixtures administered to LBW infants (1.1 kg birth weight, 29 weeks' gestation) for 5-52 days due to a variety of medical and surgical conditions. Parenteral Ca and P at 15 mM each, compared with 5 mM concentrations, when administered at approximately 125 ml/kg/day, resulted in normalized serum P and 1,25-dihydroxyvitamin D concentrations, lower urinary Ca/creatinine ratios and % TRP that remained <90%.…”
Section: Paren Teral Nutritionmentioning
confidence: 99%
“…Although published guidelines suggest that the Ca and P composition of parenteral nutrition mixtures should be 12.5-15 and 12.9-14.5mM, respectively, recent studies indicate that concentrations of Ca and P, 20 mM each, are achievable and potentially beneficial for bone mineralization (8, 9,13). These newer approaches are practical only under conditions in which the constituents of the parenteral nutrition solutions are controlled to allow solubility of Ca and P. For example, the total quantity of amino acids (>2.2 g%, as TrophAmine, Kendall-McGaw Laboratories, Irvine, CA, USA and Aminosyn-PF, Abbott Laboratories, Chicago, IL, USA) with the addition of cysteine hydrochloride (added as 30-40 mg/g amino acids) promote greater solubility of Ca and P, principally because of a lowered pH (8, 9,15). Storage time and temperature, type and concentration of mineral salts, and the order in which the salts are mixed, are important factors that affect the solubility of parenteral Ca and P (12,(15)(16)(17).…”
Section: Paren Teral Nutritionmentioning
confidence: 99%
“…Amounts of calcium and phosphorus are initiated at maintenance levels and advanced when energy and protein intakes are adequate to support intrauterine accretion rates of lean tissue [29]. The adequacy of these nutrients from PN solutions has been studied extensively in the premature population and in-depth discussions appear elsewhere [30,31,[68][69][70][71][72].…”
Section: Major Mineralsmentioning
confidence: 99%